Handbook of Technical Textiles. Vol. 2, - Horrocks, A. Richard; Anand, Subhash C. (Woodhead publishing in textiles., 2016)
With revised and updated coverage, this two-volume, second edition of the 'Handbook of Technical Textiles' reviews recent developments and new technologies across the field. Volume 2 offers an in-depth guide to established and developing areas in the use of technical textiles. The areas covered include textiles for personal protection and welfare; textiles for industrial, transport and engineering applications; and the growing area of smart textiles.